2017
DOI: 10.15390/eb.2017.6970
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions about Gamification of Education: A Q-Method Analysis

Abstract: Bu çalışma, eğitimin oyunlaştırılmasının öğrenciler tarafından nasıl algılandığını, oyunlaştırma hakkındaki öğrenci görüşlerinin ortak bir paydada birleşip birleşmediğini ve oyunlaştırmanın öne çıkan öğelerinin neler olduklarını belirlemeyi amaçlamaktadır. Bu çalışmada nicel ve nitel süreçleri bir arada içeren Q metodolojisi kullanılmıştır. Q metodolojisi, bilimsel araştırma sürecinde insanların bakış açılarını, fikirlerini, inançlarını ve tutumlarını öznel ve sistematik bir biçimde ortaya koymayı amaçlamaktad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 8 publications
2
19
0
8
Order By: Relevance
“…Music accordingly appears to have no significant effect on students' acceptance of Kahoot gamified quizzing. On the whole, the positive perceptions of students toward gamified quizzing in the present study confirm the findings of a number of studies that reported positive perceptions of students toward gamification and gamified applications (Cheong, Filippou, & Cheong, 2014;Stanley, 2014;Dizon, 2016;Zarzycka-Piskorz, 2016;Rajšp, et al, 2017;Yildirim, 2017;Ab. Rahman, et al, 2018;Bicen & Kocakoyun, 2018;Karaaslan et al, 2018;Ortega-Arranz et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Music accordingly appears to have no significant effect on students' acceptance of Kahoot gamified quizzing. On the whole, the positive perceptions of students toward gamified quizzing in the present study confirm the findings of a number of studies that reported positive perceptions of students toward gamification and gamified applications (Cheong, Filippou, & Cheong, 2014;Stanley, 2014;Dizon, 2016;Zarzycka-Piskorz, 2016;Rajšp, et al, 2017;Yildirim, 2017;Ab. Rahman, et al, 2018;Bicen & Kocakoyun, 2018;Karaaslan et al, 2018;Ortega-Arranz et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…The 22 statements that participants sorted in this study are listed in Table 1. The statements in a Q study can be formed by taking them directly from the related literature (Young and Shepardson, 2018) or they are produced by the researcher if the literature on the subject is limited (Yıldırım, 2017). In this study, the related literature was examined, and categories affecting individuals' decision-making processes regarding SSIs were determined.…”
Section: The Q Sort Designmentioning
confidence: 99%
“…Educators often seek new pedagogical tools that can increase learners' interest in learning, motivation, and active engagement with learning content. In this regard, the adaptation of digital computer games has been found to be more fun and attractive for students compared to traditional learning methods (Attali & Arieli-Attali, 2015;Yıldırım, 2017). Gamification has been defined in the literature as the use of game mechanics, features (such as badges, rewards, points, and leaderboards), and game thinking in a non-gaming context (Akpolat & Slany, 2014;Alsawaier, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, gamification is not restricted purely to younger learners (da Rocha Seixas et al, 2016;Lo & Hew, 2018). Due to the positive results that gamification has already produced, a move towards its use in higher education is well underway worldwide (Akpolat & Slany, 2014;Buckley & Doyle, 2017;Cheong et al, 2014;Yıldırım, 2017). However, a challenge posed by gamification to educators in higher education is finding an effective method of application to promote students' interest in learning, engagement, and collaborative skills (Rapp et al, 2019).…”
Section: Introductionmentioning
confidence: 99%